Front Cover: Development and Validation of 2D Difference Intensity Analysis for Chemical Library Screening by Protein‐Detected NMR Spectroscopy (ChemBioChem 5/2018). (16th February 2018) - Egner, John M.; Jensen, Davin R.; Olp, Michael D.; Kennedy, Nolan W.; Volkman, Brian F.; Peterson, Francis C.; Smith, Brian C.; Hill, R. Blake
Abstract : The front cover picture shows chemical fragment‐based screening by a 2D protein‐detected nuclear magnetic resonance approach. A novel scoring metric, difference intensity analysis (gray, yellow, and blue bar plot), was developed to quantitate NMR spectral changes and discriminate between compounds according to whether they gave rise to hits, non‐hits, or nonspecific NMR crosspeak broadening due to aggregation. More information can be found in the full paper by R. B. Hill et al. onpage 448 in Issue 5, 2018 (DOI:10.1002/cbic.201700386 ).